Seroprevalence of leptospirosis among military dogs from Johor, Malaysia - Chong, Byron Yeu Liang (2017)
Canine leptospirosis is a well-known bacteria zoonotic disease with worldwide distribution. A study on seroprevalence of canine leptospirosis was carried out in a dog population (n=40) consisted of 13 searcher dogs, 15 tracker dogs, and 12 guard dogs in Military Camp, Johor, Malaysia. A total of forty blood sera were obtained and examined by Microscopic Agglutination Test (MAT) against ten Leptospiraserovar (Canicola, Pomona, Icterohaemorrhagiae, Grippotyphosa, Lai, Australis, Pyrogenes, Javanica, Bataviae, and Celledoni) with titres ≥ 1:80 were recorded as positive results. A seroprevalence rate of 37.5% was observed in this study. LeptospirainterrogansserovarIcterohaemorrhagie 15% (n=6/40) was found to be most prevalent serovar followed by Grippotyphosa 12.5% (n=5/40), Pomona 5% (n=2/40), and Canicola 5% (n=2/40). All seropositive dogs were searchers (n=9/40) and trackers (n=6/40), and guard dogs were all seronegative. Paired-serumsamples were obtained, but there is no detection of four-fold increase in MAT. In this study, working environment, and food contamination were believed as the sources of infection in this population of military dogs. To prevent and control of canine leptospirosis in Malaysia, commercial vaccines against the four major serovars of Canicola, Pomona, Icterohaemorrhagiae, and Grippotyphosa in all military dogs is highly recommended.